Tumor necrosis factor (cachectin) mediates induction of cachexia by cord factor from mycobacteria. - Silva, C L (1988)
The mechanism by which cord factor (CF), a toxic glycolipid from mycobacteria, induces cachexia was studied in BALB/c mice. Body weight was markedly reduced 48 h after CF administration; the animals became severely wasted and exhibited hypertriglyceridemia, hypoglycemia, and high levels of tumor necrosis factor (TNF) in plasma. After CF administration, a transferable factor which caused cachexia and hypertriglyceridemia in recipient mice was detected in the blood. Dexamethasone partially inhibited the cachexia-inducing action of CF. Conditioned medium from adherent peritoneal cell cultures incubated with CF produced the same wasting symptoms when inoculated intravenously into mice. These studies also demonstrated that adherent peritoneal cells produced a humoral factor in response to CF which was related to CF-induced cachexia. Antiserum to recombinant TNF-alpha prevented the cachectin action in passive-transfer experiments. Our findings indicate that cachectin (TNF) plays a role as a central mediator of the wasting induced by CF.